How competent do teachers feel instructing self-regulated learning strategies? Development and validation of the teacher self-efficacy scale to implement self-regulated learning. (April 2018) - De Smul, Mona; Heirweg, Sofie; Van Keer, Hilde; Devos, Geert; Vandevelde, Sabrina
Abstract: This study describes the development of a self-report instrument: the Teacher Self-Efficacy Scale to implement Self-Regulated Learning (TSES-SRL). The TSES-SRL assesses teachers' perceived ability of implementing SRL as a specific instructional domain. The process of the item and scale development is presented. Exploratory factor analysis suggests a four-factor structure. Next, confirmatory factor analysis was performed and goodness of fit estimates were calculated, indicating an acceptable fit. Further, comparing the TSES-SRL to The Ohio State Teacher Efficacy Scale reveals the domain-specificity of the instrument. Overall, the TSES-SRL is considered a useful instrument to measure teachers' feelings of competence regarding SRL implementation. Highlights: The scale development of an SRL teacher-efficacy scale (TSES-SRL) is reported. The TSES-SRL has an acceptable fit and can be used in further research on SRL. Teaching SRL is considered a distinct domain of functioning in classroom practice. Teachers feel more uncertain instructing SRL than more general classroom practices.